Lessons from the Army's Future Combat Systems Program - Pernin, Christopher G. (RAND Corporation, 2012)
The U.S. Army's Future Combat Systems program aimed to field an ambitious system of systems, with novel technologies integrated via an advanced wireless network. The largest and most ambitious planned acquisition program in the Army's history, it was cancelled in 2009, and some of its efforts transitioned to follow-on programs. This report documents the program's complex history and draws lessons from its experiences.